Pharmacokinetic/pharmacodynamic evaluation of linezolid in hospitalized paediatric patients: a step toward dose optimization by means of therapeutic drug monitoring and Monte Carlo simulation. - Cojutti, Piergiorgio; Maximova, Natalia; Crichiutti, Giovanni; Isola, Miriam; Pea, Federico (J Antimicrob Chemother, 2015)
OBJECTIVES: To report on linezolid exposure in a paediatric population who routinely underwent therapeutic drug monitoring (TDM) for dosage optimization and to assess the factors affecting interpatient variability. METHODS: We performed a retrospective study of patients whose plasma C(min) and Cmax levels were measured during linezolid treatment. Adequate exposure was defined as a C(min) of 2-7 mg/L and/or an estimated AUC24 of 160-300 mg · h/L. Patients were divided into two subgroups (Group 1, 2-11 years; Group 2, 12-18 years). Monte Carlo simulation was performed to investigate whether or not the currently recommended dosages might enable a high probability of target attainment (PTA) of two thresholds for linezolid efficacy (AUC24/MIC ≥ 80 or ≥ 100). Data on demographic characteristics, disease, microbiology and haematochemical parameters and outcomes were collected. RESULTS: A total of 23 patients were included. Standard dosages were suboptimal in 50.0% and 44.4% of patients in Group 1 and Group 2, respectively. Among those who underwent multiple instances of TDM, the dosages were increased in 33.3% of cases in both groups, and decreased in 6.6% and 9.5% of cases in Group 1 and Group 2, respectively. Co-treatment with phenobarbital, proton pump inhibitors and amiodarone accounted for most of the variability in C(min) (adjusted R(2) of 0.692). Simulations showed a PTA of ≥ 90% with the current dosing regimens in both groups only for pathogens with an MIC ≤ 1 mg/L. CONCLUSIONS: Higher dosages of linezolid may be needed, especially in Group 1 when in the presence of pathogens with an MIC >1 mg/L. The role of TDM should be encouraged for optimization of linezolid exposure in the paediatric setting in the presence of infections caused by pathogens with borderline susceptibility and/or for patients co-treated with drugs that may alter linezolid exposure.
Keywords: Acetamides; Anti-Bacterial Agents; Area Under Curve; Child; Child, Preschool; Drug Monitoring; Female; Gram-Positive Bacterial Infections; Hospitalization; Humans; Infant; Inpatients; Linezolid; Male; Monte Carlo Method; Oxazolidinones; Plasma; Retrospective Studies; Tertiary Care Centers